Loss of cutaneous large and small fibers in naive and L-dopa–treated PD patients. (22nd August 2017) - Nolano, Maria; Provitera, Vincenzo; Manganelli, Fiore; Iodice, Rosa; Stancanelli, Annamaria; Caporaso, Giuseppe; Saltalamacchia, Annamaria; Califano, Francesca; Lanzillo, Bernardo; Picillo, Marina; Barone, Paolo; Santoro, Lucio
Abstract : Objective: To study small and large fiber pathology in drug-naive and L-dopa–treated patients affected by Parkinson disease (PD) in early phases, before the occurrence of neuropathic electrophysiologic abnormalities. Methods: We enrolled 85 patients with idiopathic PD (male/female 49/36, age 61.3 ± 9.7 years) without electrophysiologic signs of neuropathy, including 48 participants naive to L-dopa treatment. All patients underwent clinical, functional, and morphologic assessment of sensory and autonomic nerves through dedicated questionnaires, quantitative sensory testing, sympathetic skin response, dynamic sweat test, and punch biopsies from glabrous and hairy skin. Sensory and autonomic innervation was visualized with specific antibodies and analyzed by confocal microscopy. Data were compared with those obtained from sex- and age-comparable healthy controls. In 35 patients, skin biopsies were performed bilaterally to evaluate side-to-side differences. Results: Intraepidermal nerve fiber density was lower in patients compared to controls in all the examined sites ( p < 0.001). The loss was higher in the more affected side ( p < 0.01). A loss of autonomic nerves to vessels, sweat glands, and arrector pili muscles and of Meissner corpuscles and their myelinated endings in glabrous skin was found ( p < 0.001). Patients showed increased tactile and thermal thresholds, impairment of mechanical pain perception, and reduced sweat output ( p < 0.001). The naive and L-dopa–treated groups differed only for Meissner corpuscle density ( p < 0.001). Conclusions: Both large and small fiber pathology occurs in the early stages of PD and may account for the sensory and autonomic impairment. L-Dopa affects the 2 populations of fibers differently.